1995
DOI: 10.1139/b95-241
|View full text |Cite
|
Sign up to set email alerts
|

Global regulation of sulfur assimilation in Neurospora

Abstract: A complex regulatory circuit controls expression of many permeases and enzymes involved in sulfur assimilation in the filamentous fungus Neurospora crassa. CYS3, the global positive-acting sulfur regulatory protein, turns on the expression of structural genes that encode sulfur enzymes when N. crassa cells are limited for sulfur. Expression of the cys-3 gene itself is highly regulated by negative-acting sulfur-controller scon genes and by autogenous regulation. The CYS3 protein is localized within the nucleus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Our results indicate that control of cys-74 depends pri- (Marzluf et a/., 1995), which agrees with their relative physiological importance in vivo. It appears that the 1.4kbp upstream region of the cys-74 gene contains all the regulatory elements necessary for sulphur-responsive regulation, and that one strong CYS3binding site suffices for this control.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our results indicate that control of cys-74 depends pri- (Marzluf et a/., 1995), which agrees with their relative physiological importance in vivo. It appears that the 1.4kbp upstream region of the cys-74 gene contains all the regulatory elements necessary for sulphur-responsive regulation, and that one strong CYS3binding site suffices for this control.…”
Section: Discussionsupporting
confidence: 84%
“…Site C, 1.4 kb upstream of the transcriptional start site (tss), is actually composed of two adjacent CYSB recognition elements and has the strongest protein-binding ability. Site 6, located 1 kb upstream of the cys-14 gene, binds to CYS3 with a lower affinity than does site C. Site A, located at -150, has only weak CYS3 protein-binding ability (Marzluf et a/., 1995;Li and Marzluf, 1996). It was suggested that these DNA-binding sites might be involved in the transcriptional activation by CYSB protein (Fu and Marzluf, 1990).…”
Section: Introductionmentioning
confidence: 99%